The psychomotor vigilance task for assessing the effects of motion sickness and its treatment - Geimer, Shireen; Niemczak, Christopher E.; Howard, Patrick T.; Basner, Mathias; Buckey, Jay C. (Frontiers in Space Technologies, 2025)
BackgroundMotion sickness drugs can improve symptoms but also cause drowsiness and reduce performance as side effects. We assessed whether the psychomotor vigilance task (PVT) could provide an objective performance measure when motion sickness occurs and when drugs are used to prevent motion sickness.MethodsData were from a previously published placebo-controlled study of chlorpheniramine (C) or chlorpheniramine plus ephedrine (CE). Participants did the PVT before drug/placebo, after drug/placebo, and after provocative motion in an off-vertical axis rotation chair. Eighteen individuals were randomized to receive one of six different orders of placebo, C, or CE. Data were analyzed using linear mixed effect models and repeated measures ANOVAs.ResultsMean and median response speeds were significantly reduced after chair rides for the placebo condition indicating the PVT was sensitive to motion sickness effects. C and CE both improved motion sickness symptoms but response speeds post motion with C were significantly worse than CE post ride measures.ConclusionEphedrine given with C negated the response speed effects from C alone and enabled subjects to sustain vigilance after drug treatment. The PVT offered an objective assessment of the effects of both motion sickness and effects of motion sickness treatment on attention and vigilance.